Impact of Nutritional Counseling on Dietary Intake, Nutritional Status and Muscle Mass in Cancer Patients Undergoing Radiotherapy - Erliana, Ummu Ditya; Kurniasari, Fuadiyah Nila; Ariestiningsih, Ayuningtyas Dian (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Malnutrition in cancer patients undergoing radiotherapy can worsen outcomes. This study analyzed the effect of nutrition counseling on macronutrient intake, BMI, and muscle mass using a randomized controlled trial with intervention and control groups. Measurements were taken before and after intervention using 24-hour dietary recall, BMI, and bioelectrical impedance analysis. Data were analyzed with Wilcoxon Signed-Rank and Mann–Whitney U tests.. The results indicated that nutrition counseling improved nutritional status and muscle mass in intervention group. However, the increases in mean values across all variables were not statistically significant, including energy intake (from 1041.0 ± 359.7 to 1102.6 ± 418.7 kcal; p = 0.406), protein intake (from 40.2 ± 15.4 to 40.1 ± 18.1 g; p = 0.977), BMI (from 24.2 ± 4.6 to 24.7 ± 4.6; p = 0.087), as well as muscle mass across various body segments such as whole body (from 23.9 ± 4.7 to 24.2 ± 3.3 kg; p = 0.832), leg (from 36.6 ± 7.2 to 37.5 ± 5.2 kg; p = 0.221), arm (from 26.1 ± 6.6 to 27.0 ± 5.7 kg; p = 0.194), and trunk (from 18.2 ± 4.4 to 18.4 ± 3.4 kg; p = 0.769).Further research with a more robust study design and a multimodal approach is recommended to optimize nutritional interventions in cancer patient care.